The impact of applications on mathematics : Proceedings of the forum of mathematics for industry 2013 - Anderssen, Robert S.; Cheng, Jin; Fukumoto, Yasuhide; McKibbin, Robert; Polthier, Konrad; Takagi, Tsuyoshi; Toh, Kim-Chuan; Wakayama, Masato (Mathematics for Industry, 2014)
This book is a collection of papers presented at the Forum "The Impact of Applications on Mathematics" in October 2013. It describes an appropriate framework in which to highlight how real-world problems, over the centuries and today, have influenced and are influencing the development of mathematics and, thereby, how mathematics is reshaped, in order to advance mathematics and its application. The contents of this book address productive and successful interaction between industry and mathematicians, as well as the cross-fertilization and collaboration that result when mathematics is involved with the advancement of science and technology.